KORELASI TINGKAT PENGETAHUAN MAHASISWA MENGENAI MARGA-MARGA BATAK TERHADAP PERILAKU NALILU DI FAKULTAS PERIKANAN DAN ILMU KELAUTAN - Yuvika "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Knowledge is the result out end this happened after people take action on a particular object. This study aims to determine the level of student knowledge marga-marga Batak to determine the correlation between the level of knowlwdge od students about the marga-marga Batak against nalilu behavior. Marga is a group of unilinear kinship patrilinear, which would the be passed on to offspring continuously. Nalilu is a condition in which a vagabond who does not know the clan and lineage, so he did not know where kinship and behave according to the rules of life armpits surname. The research method used is quantitative and analyzed the correlation of product moment to compare the level knoeledge of students about the marga-marga Batak on the behavior nalilu. The result of the student’s knowledge level clans Batak was 57 (85%) of respondents in the medium category and 10 (15%) of respondents in the low category. Nalilu behavior in the evironment as much as 6 (9%) respondents never do nalilu and 46 (69%) sometimes never do nalilu and 15 (22%) of respondents have never done nalilu. Students who never did nalilu reasons if it met the hobo, it will immediately ask whether the people of his clan by clan related. If anything, call khinsip what to use. In addition, some students argued that they never intoduced clan. In this case means, they do not use rhe clan as her identy. Result of data analysis can be concluded that there is a correlation between the level of knowledge of students about the clans hobo againts nalilu behavior with significant value 0.000 lebih kecil 0,05 and the degree of influence between the two variables that are in the strong category is 0.671.Keywords: Correlation, Knowledge, Marga, Nalilu